Partners in Leaky Gut Syndrome: Intestinal Dysbiosis and Autoimmunity - Kinashi, Yusuke; Hase, Koji (Frontiers in Immunology, 2021)
The intestinal surface is constitutively exposed to diverse antigens, such as food antigens, food-borne pathogens, and commensal microbes. Intestinal epithelial cells have developed unique barrier functions that prevent the translocation of potentially hostile antigens into the body. Disruption of the epithelial barrier increases intestinal permeability, resulting in leaky gut syndrome (LGS). Clinical reports have suggested that LGS contributes to autoimmune diseases such as type 1 diabetes, multiple sclerosis, rheumatoid arthritis, and celiac disease. Furthermore, the gut commensal microbiota plays a critical role in regulating host immunity; abnormalities of the microbial community, known as dysbiosis, are observed in patients with autoimmune diseases. However, the pathological links among intestinal dysbiosis, LGS, and autoimmune diseases have not been fully elucidated. This review discusses the current understanding of how commensal microbiota contributes to the pathogenesis of autoimmune diseases by modifying the epithelial barrier.